Dukungan Sosial Dan Pospartumblues Pada Ibu-Ibu Pasca Melahirkan - Yuriadi, Yuriadi; Yanuar, Rizqi (Fakultas Agama Islam Universitas Wiralodra, 2024)
Postpartum is a mild disorder that can attack an individual's mental state after giving birth. The method used in this research is quantitative. Quantitative methods are research methods that are based on a positivist and correlational approach. Correlational research is research that focuses on finding out whether there is a relationship between two variables, namely the independent variable and the dependent variable. The independent variable is social support (X), and the dependent variable is postpartum blues (Y). The research subjects were 30 people who were mothers who had given birth in Surabaya. The results of the research show that there is a significant relationship between social support and postpartum in postpartum mothers in Surabaya with a correlation coefficient (rxy) = 0.038 and a significant p value of p= 0.083 (p>0.05), which means that the more The higher the social support obtained, the lower the postpartum experience.